2001
DOI: 10.1103/physrevb.65.014506
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of superconductivity and antiferromagnetism inCeRh1xCoxet al.

Abstract: Single-crystal specimens of CeRh 1Ϫx Co x In 5 have been investigated by means of specific heat, electrical resistivity, and magnetic susceptibility measurements as a function of temperature. The measurements reveal the occurrence of superconductivity in compounds with 0.4рxр1.0 with superconducting transition temperatures between ϳ1 and 2 K and antiferromagnetic order in compounds with 0.2рxр0.6 with Néel temperatures between ϳ3 and 4 K. Superconductivity and antiferromagnetism appear to coexist for concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
106
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(115 citation statements)
references
References 13 publications
8
106
1
Order By: Relevance
“…[13][14][15][16][17][18] Furthermore, the existence of the AFM-QCP at ∼ H c2 is strongly suggested from the observations of the NFL behavior in the paramagnetic phase above H c2 , including the − ln T divergence in specific heat divided by temperature, the T -linear dependence in magnetization, and electrical resistivity. 10,19,20) In fact, the long-range AFM orders are generated by substituting the ions for the elements in CeCoIn 5 , such as Nd for Ce, 21,22) Rh for Co, [23][24][25][26] and Cd, Hg, and Zn for In. [27][28][29][30] In contrast to the doping effect by those ions, the substitution of Sn for In simply suppresses the SC phase without generating the AFM order.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Furthermore, the existence of the AFM-QCP at ∼ H c2 is strongly suggested from the observations of the NFL behavior in the paramagnetic phase above H c2 , including the − ln T divergence in specific heat divided by temperature, the T -linear dependence in magnetization, and electrical resistivity. 10,19,20) In fact, the long-range AFM orders are generated by substituting the ions for the elements in CeCoIn 5 , such as Nd for Ce, 21,22) Rh for Co, [23][24][25][26] and Cd, Hg, and Zn for In. [27][28][29][30] In contrast to the doping effect by those ions, the substitution of Sn for In simply suppresses the SC phase without generating the AFM order.…”
Section: Introductionmentioning
confidence: 99%
“…Further, pressure-dependent and doping-dependent studies have revealed extremely rich phase diagrams that include the microscopic coexistence of superconductivity and magnetism. [4][5][6][7] Quite recently, superconductivity has also been reported in isostructural PuCoGa 5 and PuRhGa 5 . 8,9 Although less is known about these plutonium-based materials, the underlying physics appears to be similar 10 to that of CeMIn 5 and, in particular, seems to rely on the existence of at least partially localized f electrons.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Quite recently, superconductivity has also been reported in isostructural PuCoGa 5 and PuRhGa 5 . 8,9 Although less is known about these plutonium-based materials, the underlying physics appears to be similar 10 to that of CeMIn 5 and, in particular, seems to rely on the existence of at least partially localized f electrons. [11][12][13] A family of uranium-based analogues of CeMIn 5 and PuMGa 5 was reported some time ago.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By substituting Co onto the Rh site in CeRhIn 5 , we demonstrated the CeCoIn 5 is indeed near to an antiferromagnetic QCP [158,159]. We tracked both T N and T c in the electrical resistivity, specific heat and magnetic susceptibility over the entire doping range and established that the AFM state in CeRh 1−x Co x In 5 persists up to a critical concentration x c ≈ 0.75 where T N is suppressed to zero.…”
Section: Cein 3 and Cemin (M = Co Ir Rh)mentioning
confidence: 90%